A core‐transient framework for trait‐based community ecology: an example from a tropical tree seedling community. (3rd April 2017) - Umaña, Maria Natalia; Zhang, Caicai; Cao, Min; Lin, Luxiang; Swenson, Nathan G.
Abstract: Trait‐based studies in community ecology have generally focused on the community as a unit where all species occur due to stochasticity, determinism or some mixture of the two. However, the processes governing population dynamics may vary greatly among species. We propose a core‐transient framework for trait‐based community studies where a core group of species has a strong link to the local environment while transient species have weaker responses to the environment. Consistent with the expectations of the framework, we found that common species exhibit clear linkages between performance and their environment and traits while rare species tend to have weaker or non‐significant relationships. Ultimately, trait‐based ecology should move beyond applying a set of processes to a community as a whole and towards quantifying inter‐specific variation in the drivers of population dynamics that ultimately scale up to determine community structure.